Tell me your socially responsible practices, I will tell you how attractive you are! The impact of perceived CSR on organizational attractiveness - Duarte, Ana Patrícia; Gomes, Daniel Roque; Neves, José Gonçalves das (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This experimental study seeks to contribute to extending the current knowledge about the impact of corporate social responsibility (CSR) on organizational attractiveness (OA) by analyzing the mediating role of corporate image (CI). Previous literature suggests that CSR is positively related to CI and that CI is positively related to OA, but no study has empirically tested this. Participants (n=195) randomly received an individual survey containing a description of a company as fulfilling (high engagement condition) or not fulfilling (low engagement condition) a set of socially responsible practices and questions about the study variables. Structural equation modeling analyses reveal that the proposed model has a strong fit to the data, evidencing that the perceived level of engagement in CSR practices contributes to triggering the process that leads individuals to evaluate an organization as a good place to work. Accordingly, to attract candidates, information related to CSR should be considered by recruiters.